2005
DOI: 10.1063/1.1951567
|View full text |Cite
|
Sign up to set email alerts
|

Velocity profiles, stresses, and Bagnold scaling of sheared granular system in zero gravity

Abstract: We report the results of three-dimensional molecular dynamics simulations of sheared granular system in a Couette geometry. 1 The simulations use realistic boundary conditions that may be expected in physical experiments. For a range of boundary properties we report velocity and density profiles, as well as forces on the boundaries. In particular, we find that the results for the velocity profiles throughout the shearing cell depend strongly on the interaction of the system particles with the physical boundari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
2
15
1
Order By: Relevance
“…The width of the distribution decays more rapidly than expected from the Cen-tral Limit Theorem (CLT) for uncorrelated forces, which is in contrast to alternative previous observations [31,32] on sheared, dynamic, and frictional particle systems.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The width of the distribution decays more rapidly than expected from the Cen-tral Limit Theorem (CLT) for uncorrelated forces, which is in contrast to alternative previous observations [31,32] on sheared, dynamic, and frictional particle systems.…”
Section: Discussioncontrasting
confidence: 53%
“…In our study we will therefore simplify by switching off friction and shear and, instead of varying particle size, we measure the pressure at the walls with pressure-cells of different sizes. Baran and Kondic [32], on the other hand, observed that the width of the distribution decays slower than for un-correlated forces for larger averaging times and attribute this to the absence of zero-force contacts. Their system, however, was sheared in the collisional and thus dynamic regime, unlike the quasi-static isotropically stressed situation considered in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of this model for the coefficient of restitution are discussed and demonstrated in Refs. [15,18,19,20,21,22]. We have set ǫ = 0.6, because this value gives the best agreement in terms of particle compaction observed in similarly agitated states in experiments with nylon balls and in our simulations.…”
Section: B System Parametersmentioning
confidence: 99%
“…We note that recent experiments [5] on granular media undergoing planar cyclic shear do show slow evolution; however, further experiments are required. Similarly, simulations of frictional granular media undergoing Couette flow in 3D have reported significant time evolution of the measured velocity profiles [21]. To quantify the shape of the velocity profiles as a function of time, we define the degree of nonlinearity as…”
Section: A Time Evolution Of Velocity Profilesmentioning
confidence: 99%